2019 Elijah High Altitude Balloon Payload: Electronic Failure at Altitude, Applications of Turbulence and Sonification of Data - Hennigan, Nicholas McWilliam; Beaty, Chance; Endres, Eileen; Schuler, Daniel; Washburn, D'Amoure; Wolfgramm, Katherine (Proceedings of the Wisconsin Space Conference, 2020)
The 2019 WSGC Elijah High-Altitude Balloon Payload Fellowship focused on 4 high-altitude phenomena: Modular Payload Design, Applications of Air Turbulence (power generation and visualization), Electronic Behavior at Altitude, and Sonification of Atmospheric Data. Modular payload design focused on user-accessibility by creating friction-reducing rings in-between insulation and the instrumentation capsule. Height-adjustable, modular shelving was also constructed. Turbulence and Electronics project both suffered data loss during flight. However, post-flight lab analysis showed the power generation apparatus produced 96J – 120J and turbulence visualization’s potential to assist in calculating Eddie dissipation rates. Additionally, Electronic Behavior observed corona discharges across large electrical gaps near-vacuum pressures. Sonification of Data used computer algorithms to transcribe data relationships into music. The intent was to allow users to perceive data relationships and patterns aurally.